Temporal Analysis of Mangrove Canopy Cover of High Resolution Satellite Imagery on the West Coast of Bangkalan Regency, Madura East Java - Hanifa, Siti Nur; Rachman, Herlambang Aulia; Hidayah, Zainul (Jurnal Kelautan Tropis, 2024)
Mangroves are plants that live in muddy substrates, muddy sand, sand to tidal areas. These plants have important roles for marine organisms, carbon sequestration, as shoreline protectors from waves or erosion and sediment filters before entering the sea. The influence of human activity in the form of conversion of mangrove land to other forms or caused by natural disasters is a dangerous threat to the mangrove ecosystem. The magnitude of mangrove cover change is an important component so information is needed on changes in the spatial and temporal distribution of mangrove cover. This study aims to temporally analyze mangrove cover using high-resolution satellite imagery on the West Coast of Bangkalan Regency. This research uses secondary data in the form of Planetscope high-resolution satellite images from 2018 - 2023. The data will be processed to determine changes in mangrove area using Fv (Fractional Vegetation Cover). Calculation of the Fv (Fractional Vegetation Cover) value is done from the results of the minimum and maximum values of NDVI (Normalized Difference Vegetation Index). The results showed that there was a change in mangrove cover which was initially included in the FVC (Full Vegetation Coverage) class in 2022 with an area of 41.12 Ha to the HVC (High Vegetation Coverage) class with an area of 84.82 Ha in 2020. At the Arosbaya location, the highest Fv value occurred in 2019 with an area of 206.48 Ha. Reduction of mangrove area occurred in Sepulu and Arosbaya sub-districts due to land use change and sedimentation.